O conforto térmico: um contexto para estudar termologia no ensino médio - Maia, Aldecir Peixoto (Universidade Federal Rural do Semi-Árido, 2020)
In the present work, carried out under the National Professional Master's Degree in Physics Education (MNPEF), at the Federal Rural University of Semi-Arid (UFERSA), and applied to a second-year class of the morning high school at Escola Novo Mundo (ENOM), in the city of Baraúna / RN, we present a didactic sequence, with twelve classes of 40 minutes each, about thermology fundamentals, contextualized in the conception of thermal comfort in closed environments. Learning situations are presented aiming at the attribution by the students of meanings to physical quantities related to the heat propagation, considering the most immediate living universe of these students, their residences and the school. For such, diversified didactic resources are contemplated, such as dialogued classes, videos, demonstrative experiments, the relative humidity of the air and the thermal resistance of walls, using Arduino®. This conception of the didactic sequence is in line with the theoretical references present in the pedagogical recommendations suggested in the National Curriculum Parameters for high school. The discussion of the results of the measurements of the physical quantities related to the thermal comfort, made by the students in their homes and the school, and the evaluations carried out indicate for a satisfactory accomplishment of the objectives of the present proposal of intervention in the classroom
Keywords: Propagação do calor; Conforto térmico; Experimentos com Arduino; Heat propagation; Thermal comfort; Experiments with Arduino; CIENCIAS EXATAS E DA TERRA::FISICA